MiR-373-3p促进肺腺癌细胞的侵袭转移 (Zhongguo Fei Ai Za Zhi, 2015)
BACKGROUND AND OBJECTIVE: Lung cancer is the leading cause of cancer-related deaths worldwide, and metastasis is the major cause of death in lung cancer patients. MiR-373 is closely associated with invasion and metastasis in other tumor cells. This study explored the expression of miR-373-3p in non-small cell lung cancer (NSCLC) and its effect on the invasive and metastatic capabilities of lung adenocarcinoma cells, as well as their mechanisms of action. METHODS: The expression of miR-373-3p in NSCLC tissues and lung adenocarcinoma cell lines was detected by quantitative reverse transcription polymerase chain reaction. The roles of miR-373-3p in regulating lung adenocarcinoma cell invasion and metastatic properties were analyzed with miR-373-3p mimic/inhibitor-transfected cells via Transwell chamber assay. Matrix metalloproteinase MMP-9 and MMP-14 protein levels were detected by Western blot in lung cancer cells after transfection. RESULTS: MiR-373-3p was upregulated in 51 NSCLC tissues and 5 NSCLC cell lines. Gain-of-function and loss-of-function studies showed that overexpression of miR-373-3p promoted H1299 cell migration and invasion, which resulted in upregulation of MMP-9 and MMP-14. By contrast, miR-373-3p knockdown inhibited these processes in A549 cells and downregulated the expression of MMP-9 and MMP-14. CONCLUSION: Our results demonstrated that miR-373-3p participated in the invasion and metastasis of lung adenocarcinoma cells, partly by upregulation of MMP-9 and MMP-14.